Implications in Tokyo Rakugo: A Pragmatic Study - Butet Marthalina Saragih; Siti Muharami Malayu; Diah Syahfitri Handayani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Implicature is a term what the speaker might mean, suggest or mean different from what the speaker actually said. Rakugo is a type of humor in Japanese brought by hanashika or narrator. The implicature in Tokyo rakugo uses a qualitative approach method by collecting short rakugo videos from youtube, transcribing the video speech into written form and translating it and checking the correctness of the rakugo translation to Japanese native speakers. The results obtained in this study are violations of the principle of cooperation that often arise are violations of the maxim of relevance and manner, because often the rakugo utterances are not relevant to what is asked and ordered by the speaker.